Statistical and thermal physics : an introduction - Hoch, M. J. R. 1936- (CRC Press, 2011)
"Concepts and relationships in thermal and statistical physics form the foundation for describing systems consisting of macroscopically large numbers of particles. Developing microscopic statistical physics and macroscopic classical thermodynamic descriptions in tandem, Statistical and Thermal Physics: An Introduction provides insight into basic concepts at an advanced undergraduate level. Highly detailed and profoundly thorough, this comprehensive introduction includes exercises within the text as well as end-of-chapter problems. The first section of the book covers the basics of equilibrium thermodynamics and introduces the concepts of temperature, internal energy, and entropy using ideal gases and ideal paramagnets as models. The chemical potential is defined and the three thermodynamic potentials are discussed with use of Legendre transforms. The second section presents a complementary microscopic approach to entropy and temperature, with the general expression for entropy given in terms of the number of accessible microstates in the fixed energy, microcanonical ensemble. The third section emphasizes the power of thermodynamics in the description of processes in gases and condensed matter. Phase transitions and critical phenomena are discussed phenomenologically.In the second half of the text, the fourth section briefly introduces probability theory and mean values and compares three statistical ensembles. With a focus on quantum statistics, the fifth section reviews the quantum distribution functions. Ideal Fermi and Bose gases are considered in separate chapters, followed by a discussion of the "Planck" gas for photons and phonons. The sixth section deals with ideal classical gases and explores nonideal gases and spin systems using various approximations. The final section covers special topics, specifically the density matrix, chemical reactions, and irreversible thermodynamics. "--Anotace od vydavatele
Keywords: termodynamika; entropie; statistická fyzika; thermodynamics; entropy; statistical physics; monografie; monographs